DISFUNGSI KESENIAN GAMAD DAN BALANSE MADAM DI SUMATERA BARAT - Febri Yulika; Susi Fitria Dewi; Jelly Jelly; Yetty Oktayanty (LPPMPP Institut Seni Indonesia Padangpanjang, 2021)
Gamad music and Balanse Madam dance are no longer popular among the people of West Sumatra. This art was created by an art movement from Nias who lived in the city of Padang in the early 18th century. Balanse Madam art was popular in the 1960s to 1980s. The specialty of this art is that it adopted the music and dance of the Portuguese who loved to party when they traded spices on the West Sumatra coast in the 18th century. The Balanse madam dance was later imitated by Nias workers who later adapted it to the values of the people of West Sumatra. The music that accompanies the Balanse Madam dance is Gamad music (Inter-Regional Music Association) combining various musical instruments of various ethnicities living in the city of Padang such as Minangkabau, Medan and Malay regional music. However, this art, both Gamad music and Balanse Madam dance, are no longer alive in society. Various factors, both internal and external, have caused this art to be rarely performed. As for this article, it will be analyzed using the concept of dysfunction. As for this article, it will be analyzed using the concept of dysfunction. AbstrakMusik Gamad dan Tari Balanse Madam sudah tidak populer lagi di kalangan masyarakat Sumatera Barat. Kesenian ini diciptakan oleh sebuah gerakan seni dari Nias yang bermukim di kota Padang pada awal abad ke-18. Seni Balanse Madam populer pada tahun 1960 hingga 1980-an. Keistimewaan kesenian ini adalah mengadopsi musik dan tarian bangsa Portugis yang gemar berpesta saat berdagang rempah-rempah di pesisir Sumatera Barat pada abad ke-18. Tari Balanse Madam ini kemudian ditiru oleh para pekerja Nias yang kemudian disesuaikan dengan nilai-nilai masyarakat Sumatera Barat. Musik yang mengiringi tari Balanse Madam adalah musik Gamad yang memadukan berbagai alat musik dari berbagai etnis yang tinggal di kota Padang seperti musik daerah Minangkabau, Medan dan melayu. Namun kesenian ini, baik musik Gamad maupun tari Balanse Madam, sudah tidak hidup lagi di masyarakat. Berbagai faktor baik internal maupun eksternal menyebabkan kesenian ini jarang dipentaskan. Adapun artikel ini dianalisis dengan menggunakan konsep disfungsi.